Conversion of propargylic amines with CO2 from flue gas using Lu2CrMnO6 supported by ionic liquid on dendritic nanosilica - Shulong Liu; Dulong Feng; Seyed Mohsen Sadeghzadeh (Journal of CO2 Utilization)
The concurrent creation of a phase interface and threadlike architecture can enhance the segregation, enzymatic efficiency, and functionality of dendritic silica fibres (DFNS). Nonetheless, a straightforward and eco-friendly fabrication method remains essential. In this study, we successfully developed a sophisticated dandelion-resembling SiO2 with an anatase/SiO2 phase interface and highly distinct surface area using a simple and environmentally benign deep eutectic solvent-modulating technique. The extensive distinct surface area is attributed to its 3D hierarchical structure, composed of 2D ultrathin nanolayers with mesoscopic cavities. We synthesized Lu2CrMnO6 nanoparticles with ionic liquid loaded on DFNS (Lu2CrMnO6@IL-DFNS) through an uncomplicated synthetic route. DFNS provided numerous -OH groups for uniform IL loading via chemical linkage, while IL adjusted the fibre dimensions and exposed dynamic adsorption sites of –NH2 groups, facilitating CO2 chemisorption. The aggregate morphology of the Lu2CrMnO6@IL-DFNS composite remained largely unchanged after Lu2CrMnO6@IL loading, maintaining its mesoporous structure, crystalline form, and chemisorptive properties. This catalyst exhibited a low incidence of 2-oxazolidinone generation during the direct synthesis from propargylic amines and CO2 owing to its limited distinct surface area and fewer active sites.